EDUKASI PEER-TO-PEER LENDING SYARIAH SEBAGAI ALTERNATIF PERMODALAN BAGI USAHA MIKRO KECIL DAN MENENGAH PADA KECAMATAN BATANG KAPAS KABUPATEN PESISIR SELATAN - Yoda, Tilawatil Ciseta; Reswita, Yefri; Darman, Darman; Suandi, Edi; Febriani, Rina; Syaiful, Syaiful (Komunitas Manajemen Kompetitif, 2024)
he Covid-19 pandemic is a condition where MSMEs are starting to look at the use of financial technology for their operational needs. Since 2016, 38% of people have used payment-based fintech, while access to fintech based on deposits, lending, and capital raising has reached 31%. Unfortunately, this increase is not accompanied by a good level of financial literacy education. In addition, there is a technological gap between urban and rural communities and also between users at a young age and those over 35 years old. So the solution to the problem offered is through technological literacy education by introducing the financial technology industry to rural communities, especially in Batang Kapeh District, Pesisir Selatan Regency. Sharia P2P lending is a technological innovation in financial services, where financial service providers can develop a technology that can change the traditional financial market to be more modern. Sharia P2P lending brings together lenders and loan seekers on one platform, where later lenders and loan seekers will get interest from the funds lent according to the agreement. The development of MSMEs usually has a common problem, namely capital problems. MSME actors are usually hampered by capital, they establish a business with limited capital, so that sometimes these MSME actors find it difficult to develop their business. Relying on banks in applying for loans for business capital is constrained by the terms and policies that are difficult for MSMEs to meet. This problem makes MSME actors inevitably look for other sources of capital that are easy to meet. Using the innovation of the Sharia FinTech peer to peer lending (P2P lending) model can be one of the capital solutions for MSME business actors. The purpose of this community service is to introduce the importance of capital in business, introduce fintech, provide financial literacy education about crowdfunding and mentoring to the community on the Sharia Peer-to-Peer Lending platform. The implementation method starts from needs analysis, filling out an initial questionnaire, core activities, then continuing with a final questionnaire, and ending with an evaluation. Through this activity, it is expected to be able to contribute to the direct economic empowerment of the community by providing solutions that can overcome partner problems. The target audience for this Community Partnership Program are business actors (SMEs) in the food industry sector, Batang Kapas District, Pesisir Selatan Regency, West Sumatra. This activity starts from planning, implementing and evaluating activities. The results of this training and mentoring activity include 1). Increasing community knowledge of aspects of business development through training in accessing market information for each SME actor, 2). Increasing knowledge and access to SME funding through the use of the Sharia P2P lending application. 3) Being able to apply the use of Sharia P2P lending technology as an alternative for business capital.